The vision of the priestly narrative: its genre and hermeneutics of time - Boorer, Suzanne (Ancient Israel and its literature, 2016)
"Boorer explores the theology of an originally independent Priestly narrative (Pg), extending through Genesis-Numbers, as a whole. In this book she describes the structure of the Priestly narrative, in particular its coherent sequential and parallel patterns. Boorer argues that at every point in the narrative's sequential and parallel structure, it reshapes past traditions, synthesizing these with contemporary and unique elements into future visions, in a way that is akin to the timelessness of liturgical texts. The book sheds new light on what this material might have sought to accomplish as a whole, and how it might have functioned for, its original audience